Metabolische Chirurgie - Billeter, Adrian; Müller, Beat P. (Der Chirurg, 2019)
In recent years the surgical treatment of metabolic diseases has become established as an effective alternative to conservative treatment. The new S3 guidelines address these changes and give clear indications for obesity surgery. One of the core points of the new guidelines is the differentiation between obesity surgery and metabolic surgery. In obesity surgery the primary aim of treatment is weight loss whereas for metabolic indications the aim is an improvement of comorbidities independent of the body mass index (BMI). With respect to the selection of procedures sleeve gastrectomy (SG) and the traditional Roux-en-Y gastric bypass (RYGB) can be used as safe and evidence-based operative procedures. The RYGB has better metabolic effects but higher complication and reintervention rates. More recent procedures, such as the one anastomosis gastric bypass (OAGB) and single anastomosis duodeno-ileal (SADI) bypass possibly have slightly stronger metabolic effects, however, the risk of malnutrition and vitamin deficiency is higher.
Gesehen am 28.11.2019